Behaviour, preferences and cities: Urban theory and urban resurgence. - Storper, Michael; Manville, Michael (Urban Studies (Routledge), 2006)
The resurgence of big, old cities and their regions is real, but it is merely a part of a broader pattern of urban change in the developed countries, whose broadest tendency is urban emergence, including suburbanisation, and movements of population to certain ‘Sunbelt’ regions. The problem is that it is difficult to accommodate explanation of both resurgence and emergence using the main explanations in the field today. These include: theories of the knowledge or creative economy, urban amenities, diversity and tolerance, and urban beauty. In most of their common specifications, they do well for either resurgent or emergent cities, but not for both at the same time. This suggests that these ideas, interesting as they are, require much greater specification and, in some cases, overhaul, in order to offer satisfactory responses to the diversity of patterns of urban growth. By examining some of these deficiencies, we conclude that urban theory needs a better understanding of urban choice behaviours and especially the effects of bundling, the limits to preference substitutions and the relationship between past and present preferences, in order to become fully effective in explaining urban resurgence and urban emergence. When these aspects of choice and preference are better integrated into urban theory, then the ‘exogenous’ causes of urbanisation can be made more endogenous and, in addition, they can be applied better to both emergence and resurgence. Urban research can, by so doing, also potentially become more policy-relevant.